PWE-031 Colonic iron chelation by alginate biopolymers for the enhancement of gastrointestinal health. (17th June 2017) - Horniblow, RD; Mistry, P; Quraishi, MN; Iqbal, TH; Tselepis, C
Abstract : Introduction: Excess, 'free iron' residing within the large bowel is known to be pro-inflammatory and associated with chemical, cellular and microbial dysregulation.(1, 2) Reports suggest that these modifications may underpin the pathogenesis of intestinal disease. The recent identification of an inert, non-digestible iron chelator (alginate Manucol LD) may prove therapeutically useful in sequestering this pool of toxic iron.(3) Thus, this study aims to assess the tolerability and acceptability of a novel Manucol LD formulation in healthy volunteers and to assess the impact on the gut microbiome. Method: Healthy volunteers (n=17) were supplemented with 3.0 g of Manucol LD per day. Blood samples were taken prior to alginate consumption, day 14 (midpoint) and day 28 (end) of the study. Stool samples were also collected at these time points and were subject to faecal microbial 16s RNA sequencing and faecal metabolome assessments using mass spectrometry. Results: Manucol LD formulation compliance was 98%. Mean bowel frequency increased from 1.2 and 1.5 motions/day respectively. No discomfort was associated with 72% of the doses, with the main side effect being excess flatulence. There were no significant changes in any haematological parameters measured (including haemoglobin, creatinine, alanine aminotransferase, calcium and magnesium). With respect to microbiome changes, a number of microbial changes occurred which were indicative of enhanced gut health. These included increases in Prevotella (12/17 individuals, p<0.05) and Akkermansia (11/17, p<0.05) with reductions in Coprococcus (12/17 p<0.05) observed. Bacteroides reduced (11/17) by midpoint by 11.0% (p<0.05). Conclusion: Manucol LD formulation was well tolerated with no associated side effects. Microbial changes were observed upon supplementation of Manucol LD suggesting that this dietary iron chelator may be able to modulate the dysregulation of the microbiome observed in disease. Whether these changes are directed through its iron chelating ability is currently being investigated. References: . Werner T, Wagner S J, Martinez I, Walter J, et al. Depletion of luminal iron alters the gut microbiota and prevents Crohn's disease-like ileitis. Gut2011;60:325–333. . Radulescu S, Brookes MJ, Salgueiro P, Ridgway RA, et al. Luminal iron levels govern intestinal tumorigenesis after Apc loss in vivo. Cell reports2012;2:270–282. . Horniblow RD, Latunde-Dada GO, Harding SE, Schneider M, et al. The chelation of colonic luminal iron by a unique sodium alginate for the improvement of gastrointestinal health. Molecular Nutrition & Food Research2016;60:2098–2108. Disclosure of Interest: None Declared